The recent areas of applicability of palladium based membrane technologies for hydrogen production from methane and natural gas: A review. (22nd February 2023) - Jokar, S.M.; Farokhnia, A.; Tavakolian, M.; Pejman, M.; Parvasi, P.; Javanmardi, J.; Zare, F.; Gonçalves, M. Clara; Basile, A.
Abstract: In the wake of the devastating consequences of climate change, many countries are searching for alternative renewable energy. Hydrogen, the most abundant element on earth, is an alternative clean and non-toxic energy source. Palladium-based membranes and their alloys are categorized as inorganic metallic membranes with the highest selectivity and permeation rate for hydrogen production. Pd-based membranes have great potential for resolving environmental concerns and adverse side effects of greenhouse gases resulting from industrial processes. This paper analyses Pd-based membranes and their industrial applications while focusing on natural gas and methane as non-renewable feedstocks for hydrogen production. Steam reforming of natural gas and methane, partial oxidation reaction, auto thermal reforming, dry reforming, and gas to liquid process are among the processes that take place in a Pd-based membrane reactor and are discussed in this paper. Finally, all the ongoing research and development on both laboratory and industrial scales are reviewed. Highlights: The role of hydrogen as a sustainable and alternative energy vector is highlighted. The use of Pd membrane and its alloys for methane and natural gas reforming processes is discussed. The mainstream approaches to the production of hydrogen from methane and natural gas are reviewed. The current industrial applications of palladium membrane reactors are presented.